Desafios e possibilidades : a compreensão do diálogo que se constrói entre escola e famílias - Santos, Jônatas Marcos da Silva (2016)
This construction is the result of dialogue and research under the master`s degree in education PPGEdu/UFMT. Its context is in wider reflections on the importance of the school´s relationship with the families and with the community to transformation of the human being and society. The basic theme for “sulear” is understanding the dialogue between school and families. Looking for understanding the challenges and possibilities toward the proposals that advocate greater participation of families in the recreation of a dialogical and ethics education, with a view to communion of mankind to the building of a citizen liberating education. Based on dialectic-phenomenological concept found in Paulo Freire, it is intended to go on an investigation and create a contrast to banking education model, committed to playing the neoliberal ideology, alienating and families the possibility of getting over the dichotomy between subject and the world that mediates themselves. The main problem underlying the research is how concretely happens the dialogue between school principals, teachers and families so that the dialogue in Freire liberating education perspective may happen, it is the main goal for this research. The curious construction of this job search took place for dialogue through the interviews with managers at the Municipal Jaciara Municipality of education in the state of Mato Grosso, with school principals and teachers at the Municipal School Magda Ivana and with the student´s families of the ninth year of this school. The ones involved on the research, were six school managers, four teachers, three mothers and two fathers. The research is developed according to the qualitative critical theoretical framework. For data collection the instruments used are the dialogic semi-structured interviews. The theoreticalmethodological foundations based on in Freire (2011, 2009, 2014a/b, 2015a/b) and also in relation to theoretical frameworks and critical analysis of the data are considered Gadotti (2012, 1998, 1997); Carvalho (2005); Guareschi (1996, 2013); Streck (2003). Research in their results revealed that between challenges and school dialogue opportunities with families there are incipient personal initiatives of mutual approach of both institutions. Also showed the existence of possibilities for participation of the families in the school context and the concern of school principals and teachers in getting families to get involved in the educational process of the students. It is also realized the it is possible to make the school a fundamentally civic institution, marked by dialogical ethical values in the process of approchement of families. However, it was seen that there is a strong practice of reproductive education of the government system with neoliberal ideological apparatus, which hinders the world and the context of decisions where the educational life happens, at school and in the families that make up the society there is a delivery of the school above spheres, causing existential fatigue, discouragement and hopelessness in people who try to create actions that build dialogue and demonstrate faith in the unfinished humanity.